Morphological evolution reduces downstream displacement in juvenile landlocked salmon - Yamada, Hiroyuki; Wada, Satoshi (Dryad, 2021)
Severe flooding often leads to downstream displacement of aquatic animals.
Despite this, many salmonid populations persist in habitats located
upstream of tall barriers, such as artificial check dams and/or natural
waterfalls, that completely block fishes from returning to the upstream
areas after flooding. The evolution of such populations may be affected by
spatial sorting due to differential rates of downstream displacement. This
study examined whether a morphological trait (increased body depth) that
allows individuals to better maintain their position during flooding has
evolved in juvenile amago salmon Oncorhynchus masou ishikawae inhabiting
above-barrier habitats in two rivers. In both rivers, juveniles collected
at the stations with multiple downstream barriers had deeper bodies than
those collected at other stations. Similar differences were found in
juveniles reared in a common-garden experiment. Field experiments with
natural flooding also indicated that deep bodies help juveniles resist
downstream displacement. These results consistently suggest that juveniles
in some above-barrier habitats have evolved deep bodies to resist
downstream displacement due to flooding. Our study is the first to show
the evolutionary outcomes of passive spatial sorting during severe climate
events.
Data for Morphological evolution reduces downstream displacement in
juvenile landlocked salmon Yamada and Wada, Evolution 2021. These files
contain all data for the field survey, field experiment, and common
environment experiment. Data for the field survey and common
garden experiment are divided into two data files (i.e., Koza River data
and Hirai River data). Explanation for the variables:  Release
day (File for the field experiment):  Release group for the field
experiment ("8-Jun" and "20-Jun"corresponds to the
first and second release group, respectively).  Retention status
(File for the field experiment):  Juveniles were assigned a
retention status of 1 if they were recaptured above the first check dam,
and a retention status of 0 if they were recaptured further
downstream.   Ascent status (File for the field
experiment):  Juveniles were assigned an ascent status of 1 if
they were recaptured upstream of the uppermost step, and an ascent status
of 0 if they were recaptured further downstream.  Cage ID (Files
for the common garden experiment):  ID of the cage in which the
juveniles were raised.  Habitat group (Files for the field survey
and common garden experiment):  Attributes of each study station
regarding barriers.


Station
(Files for the field survey and common garden experiment):  Name
of each study station.  PC1 (Files for the field survey, field
experiment, and common garden experiment):  PC1 obtained by
principal component analysis of the log transformed body depth
measurements for all data (i.e., the field survey, field experiment, and
common garden experiment).  PC1 residual (Files for the
field survey, field experiment, and common garden experiment):
Residuals calculated from the predicted values of linear regression models
and the −PC1 values.   Caudal peduncle depth-1
(Files for the field survey, field experiment, and common garden
experiment):  Measurement values of the caudal peduncle depth at
the posterior end of the adipose fin.  Caudal peduncle depth-2
(Files for the field survey, field experiment, and common garden
experiment):  Measurement values of the caudal peduncle depth
from the posterior end of the anal fin to the anterior end of the adipose
fin.  Body depth-1 (Files for the field survey, field experiment,
and common garden experiment):  Measurement values of the body
depth from the lateral line to the anterior end of the dorsal fin.
Body depth-2 (Files for the field survey, field experiment, and
common garden experiment):  Measurement values of the body depth
at the anterior end of the anal fin.  Fork length (Files
for the field survey, field experiment, and common garden
experiment):  Measurement values of the fork length.
Keywords: FOS: Agriculture, forestry, and fisheries